Effect of feeding system and breed on growth performance, and carcass and meat quality traits in two continental beef breeds. (September 2015) - Avilés, C.; Martínez, A.L.; Domenech, V.; Peña, F.
Abstract: A total of 100 young bulls were allotted a 2 × 2 factorial arrangement of treatments to determine the effect of the feeding system (concentrate and wheat straw: T; total mixed ration comprised of the same concentrate, maize silage and wheat straw: TMR) and breed (Limousine: LI; Retinta: RE) on growth performance, carcass characteristics and meat quality. The diets were administrated ad libitum for 193 days. The average daily weight gain was similar (P > 0.05) for both diets, while the LI bulls grew significantly (P < 0.05) more than RE. T bulls showed higher L*, a* and rib bone percentage. TMR bulls showed higher carcass yield, conformation and fatness, and greater changes in ultrasound measurements, except Δ UGMD and rib fat percentage. Instrumental meat quality, except shear force at 1 and 21 days of ageing, was not affected (P > 0.05) by the diets. Breed significantly affected most of the analyzed characteristics. Highlights: The effect of diet and breed on growth performance, carcass and meat quality was determined. Feeding system did not affect most features analyzed (20 out of 65). It affected most post-chilling meat colour and ultrasound carcass measurements. Breed affected growth and many carcass ultrasound and conformation measurements.